Analisis Parameter Kecepatan Teoritik Dan Nilai Beda Fase Gelombang Rayleigh Lapisan Aspal Perkerasan Jalan Berdasarkan Teori Perambatan Gelombang Pada Media Yang Homogen Dan Isotropik - Sri Atmaja P Rosyidi (Semesta Teknika, 2005)
The Rayleigh wave is one of seismic waves which generated from the natural and artificial mechanical source in the earth or place on the subsurface, such as landslide, earthquake, explosion, traffic vibration, machine works, etc.  The Rayleigh wave in a possible stratified of homogeneous media is a linear combination of Primary (P) and Vertically Shear (SV) waves, which satisfied the equations of elasticity with zero body forces and zero traction on the boundary of a half-space media.  In the case of a homogeneous isotropic half-space there is a unique mode of the Rayleigh waves which propagates without being sustained by any sources or external loads.  Almost 70 % of wave energy generated from the mechanical sources is the Rayleigh wave energy.  Therefore, it is a potential characteristic of Rayleigh wave that is able to be used in engineering purposes.  One of them is a spectrum analysis that is applied in transportation engineering in order to control the quality of asphaltic material.  The aim of this paper is to predict the Rayleigh wave velocity parameters and phase different value of asphaltic layer based on a fundamental theory of Rayleigh wave propagation in a homogeneous isotopic. The results have been shown that the phase different value in homogenous isotropic media is strongly influenced by field spacing of wave measurement.  The Rayleigh wave velocity parameters were easier obtained using the simple equation considering to various Poisson value.